Signaling and polarized communication across the T cell immunological synapse - Dustin, M; Choudhuri, K (Annual Reviews, 2016)
T cells express a somatically recombined antigen receptor (αβTCR) that is calibrated during development to respond to changes in peptides displayed by major histocompatibility complex proteins (pMHC) on the surface of antigen-presenting cells (APC). A key characteristic of pMHC for adaptive immunity is the ability to sample internal states of cells and tissues to sensitively detect changes associated with infection, cell derangement, or tissue injury. Physical T cell-APC contact sets up an axis for polarization of TCR, adhesion molecules, kinases, cytoskeletal elements, and organelles inherent in this mode of juxtacrine signaling. The discovery of further lateral organization of the TCR and adhesion molecules into radially symmetric compartments, the immunological synapse, revealed an intersecting plane of symmetry and potential for regulated symmetry breaking to control duration of T cell-APC interactions. In addition to organizing signaling machinery, the immunological synapse directs the polarized transport and secretion of cytokines and cytolytic agents across the synaptic cleft and is a site for the generation and exocytic release of bioactive microvesicles that can functionally affect recipient APC and other cells in the environment. This machinery is coopted by retroviruses, and human immune deficiency virus-1 may even use antigen-specific synapses for infection of healthy T cells. Here, we discuss recent advances in the molecular and cell biological mechanisms of immunological synapse assembly and signaling and its role in intercellular communication across the synaptic cleft. Expected final online publication date for the Annual Review of Cell and Developmental Biology Volume 32 is October 06, 2016. Please see http://www.annualreviews.org/catalog/pubdates.aspx for revised estimates.